Exploiting the passenger ACO1-deficiency arising from 9p21 deletions to kill T-cell lymphoblastic neoplasia cells. (17th November 2019) - Gonzalez-Sanchez, Laura; Cobos-Fernandez, Maria A; Lopez-Nieva, Pilar; Villa-Morales, Maria; Stamatakis, Konstantinos; Cuezva, Jose M; Marin-Rubio, Jose L; Vazquez-Dominguez, Irene; Gonzalez-Vasconcellos, Iria; Salido, Eduardo; Llamas, Pilar; Lopez-Lorenzo, Jose L; et al.
Abstract: Precursor T-cell lymphoblastic neoplasms are aggressive malignancies in need for more effective and specific therapeutic treatments. A significant fraction of these neoplasms harbor deletions on the locus 9p21, targeting the tumor suppressor CDKN2A but also deleting the aconitase 1 ( ACO1 ) gene, a neighboring housekeeping gene involved in cytoplasm and mitochondrial metabolism. Here we show that reducing the aconitase activity with fluorocitrate decreases the viability of T-cell lymphoblastic neoplasia cells in correlation to the differential aconitase expression. The consequences of the treatment were evidenced in vitro using T-cell lymphoblastic neoplasia cell lines exhibiting 9p21 deletions and variable levels of ACO1 expression or activity. Similar results were observed in melanoma cell lines, suggesting a true potential for fluorocitrate in different cancer types. Notably, ectopic expression of ACO1 alleviated the susceptibility of cell lines to fluorocitrate and, conversely, knockdown experiments increased susceptibility of resistant cell lines. These findings were confirmed in vivo on athymic nude mice by using tumor xenografts derived from two T-cell lines with different levels of ACO1 . Taken together, our results indicate that the non-targeted ACO1 deficiency induced by common deletions exerts a collateral cellular lethality that can be used as a novel therapeutic strategy in the treatment of several types of cancer. Abstract : ACO1 deficiency confers a vulnerability to certain tumors that can be therapeutically exploited by using aconitase inhibitors to specifically target tumor cells.